Evaluating the Effectiveness of a Self-Management Program on Patients Living with Chronic Diseases [Letter] - Jayte M (Dove Medical Press, 2024)
Mohamed Jayte Department of Internal Medicine at Kampala International University, Kampala, UgandaCorrespondence: Mohamed Jayte, Department of Medicine, Kampala International University, P.O. Box 7062, Kampala, Uganda, Tel +256 55272543, Email jayte.mohamed@studwc.kiu.ac.ug